Ogólne założenia sowieckiej polityki okupacyjnej w Polsce - Głowacki, Albin (Pamięć i Sprawiedliwość, 2008)
The fi rst source of the USSR policy guidelines referring to the inhabitants of eastern territories of the Second Republic of Poland known to historians are included in the confi dential directives for the Red Army which invaded Poland on 17 September 1939. The details concerning the organization of the Soviet-occupied territories were prepared by the the Political Bureau of the Central Committee of the All-Union Communist party (bolsheviks) on 1 October 1939. Those guidelines constituted the basis for immediate and resolute activities undertaken by new authorities. The aim of the occupier’s policy was to unify newly annexed territories with the USSR and Sovietization of the inhabitants as quickly as possible. It meant the necessity to transform radically and on a large scale all spheres of political, social, cultural and economic life in compliance with patterns realized until that moment in the state which dealt with ‘building socialism’. The article deals with the following: changes in the administrative division (adjusting to the standards of the USSR); regulations concerning the citizenship of inhabitants of the occupied territories; personnel policy (radical changes in Polish staff – replacing them with confi dents from the East); ownership transformations and transforming the economy (nationalization of enterprises and factories, forfeiting landed gentry’s estates, division of land between smallholders and peasants without any land, creating collective farms, replacing Polish zloty with ruble, top-down planning); fi ght against religion (anti-religious upbringing and propagation of atheism among society); informative policy (monopolization of mass media, supervision of the party over mass media, censorship); restructuring of educational system and higher schools (structural, staff and curriculum-related changes, popularization of education, indoctrination by school system and teachings); nationalization of and ideologizing cultural institutions; changes in labor, social insurance, tax and health care laws. The fundamental role in the facilitation and speeding up the process of Sovietization of the mental sphere, social and economic relations, and depolonization of annexed territories was played by different reprisal forms (arrests of members of leading social and professional groups, deportations, and genocide). Soviet occupation policy was a function of relations between the USSR and the Third Reich and it was subject to evolution depending on the changes in those relations.